Sistem Informasi Globai pada Perusahaan Multinasional - Hersatoto Listiyono (Universitas Stikubank, 2003)
Multinational Corporation is company that operated in many products, markets and cultural, because they, have many company’s branch in foreign. So Multinational Corporation need Global Information System for coordinating their company's branch. Global Information System can connect between everyone involved decision making. Coordinating can done more effective and efficient with Global Information System, because Global Information System can give coordinating's support unlimited time and place.